The Impact of Wireless Emergency Alerts on a Floating Population in Seoul, South Korea: Panel Data Analysis - Sungwook Yoon; Hyungsoo Lim; Sungho Park (JMIR Publications, 2024)
BackgroundWireless emergency alerts (WEAs), which deliver disaster information directly to individuals' mobile phones, have been widely used to provide information related to COVID-19 and to encourage compliance with social distancing guidelines during the COVID-19 pandemic. The floating population refers to the number of people temporarily staying in a specific area, and this demographic data can be a useful indicator to understand the level of social distancing people are complying with during the COVID-19 pandemic. ObjectiveThis study aimed to empirically analyze the impact of WEAs on the floating population where WEAs were transmitted in the early stages of the COVID-19 pandemic. As most WEA messages focus on compliance with the government's social distancing guidelines, one of the goals of transmitting WEAs during the COVID-19 pandemic is to control the floating population at an appropriate level. MethodsWe investigated the empirical impact of WEAs on the floating population across 25 districts in Seoul by estimating a panel regression model at the district-hour level with a series of fixed effects. The main independent variables were the number of instant WEAs, the daily cumulative number of WEAs, the total cumulative number of WEAs, and information extracted from WEAs by natural language processing at the district-hour level. The data set provided a highly informative empirical setting as WEAs were sent by different local governments with various identifiable district-hour-level data. ResultsThe estimates of the impact of WEAs on the floating population were significantly negative (-0.013, P=.02 to -0.014, P=.01) across all specifications, implying that an additional WEA issuance reduced the floating population by 1.3% (=100(1-e-0.013)) to 1.4% (=100(1-e-0.014)). Although the coefficients of DCN (the daily cumulative number of WEAs) were also negative (-0.0034, P=.34 to -0.0052, P=.15) across all models, they were not significant. The impact of WEAs on the floating population doubled (-0.025, P=.02 to -0.033, P=.005) when the first 82 days of observations were used as subsamples to reduce the possibility of people blocking WEAs. ConclusionsOur results suggest that issuing WEAs and distributing information related to COVID-19 to a specific district was associated with a decrease in the floating population of that district. Furthermore, among the various types of information in the WEAs, location information was the only significant type of information that was related to a decrease in the floating population. This study makes important contributions. First, this study measured the impact of WEAs in a highly informative empirical setting. Second, this study adds to the existing literature on the mechanisms by which WEAs can affect public response. Lastly, this study has important implications for making optimal WEAs and suggests that location information should be included.